Does inchinkoto, a herbal medicine, have hepatoprotective effects in major hepatectomy? A prospective randomized study. Issue 5 (May 2015) - Mizutani, Tetsushi; Yokoyama, Yukihiro; Kokuryo, Toshio; Ebata, Tomoki; Igami, Tsuyoshi; Sugawara, Gen; Nagino, Masato
Abstract: Objectives: This randomized clinical trial was designed to investigate whether inchinkoto has a hepatoprotective effect on postoperative outcome after major hepatectomy. Methods: Sixty-one patients scheduled for major hepatectomy were randomly assigned to one of two groups in which preoperative inchinkoto was (inchinkoto group, n = 30) or was not (non-inchinkoto group, n = 31) administered. Inchinkoto was administered for at least 7 days before surgery. The primary endpoint was the incidence of post-hepatectomy liver damage. The expression of nuclear factor E2-related factor 2 (Nrf2) and other oxygen stress-related markers in the liver were also determined. Results: There was no significant difference in clinical characteristics between the inchinkoto and non-inchinkoto groups. Serum levels in liver function tests and incidences of post-hepatectomy liver failure did not differ significantly between the two groups. However, there was a significantly higher induction of antioxidant factors in the liver, such as Nrf2 protein and heme oxygenase-1 mRNA, after hepatectomy in the inchinkoto group than in the non-inchinkoto group. Conclusions: The preoperative administration of inchinkoto did not have a significant impact on the overall outcome of major hepatectomy. However, inchinkoto induced the expression of Nrf2 during hepatectomy and may have exerted an antioxidative effect on the liver.